Integrasi Produksi - Distribusi pada Supply Chain dengan Pendekatan Hybrid Analitik - Simulasi - Annisa Kesy Garside; R. Hadi Wahyuono; Tiananda Widyarini (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
Integrated production-distribution problem resolution using analytical model lacks of consideration of many uncertainties along supply chain line such as delays, queues, machine breakdown, vehicle malfunction, and environmental factor. By utilizing simulation as complex stochastic system modelling, this research aims to develop hybrid analytical-simulation approach to resolve integrated production-distribution model. Time capacity adjustment is required if production-distribution plan obtained from analytical model requires longer production and delivery time than available. The adjustment is using a procedure developed based on duration obtained from simulation model and is used to obtain adjusted time capacity. The implementation of hybrid method to resolve integrated production-distribution problem on two echelon supply chain with 2 factories and 5 DCs shows a feasible solution was obtained on the third iteration